GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG MAKANAN SEHAT UNTUK ANAK PRASEKOLAH DI TAMAN KANAK-KANAK BAHAGIA SURABAYA - Sari, Ethyca (S1 Keperawatan, 2014)
GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG MAKANAN SEHAT UNTUK ANAK PRASEKOLAHÂ  DI TAMAN KANAK-KANAK BAHAGIA SURABAYAÂ Oleh : Ethyca SariÂ ABSTRACTHealthy food is a food consisting of vegetables, protein, fruit and fibrous foods. The benefits of a healthy diet is to get the energy to perform daily physical activity and maintaining the body in the growth and development. The knowledge is the recognize result and it happens after someone do the sensing to certain object. Based on it the writer is interested to take the title âThe Descripton of Mother Knowledge Level About Healthy Food to The Preschool Children at Kindergarten Happy Surabayaâ. The purpose of this study was to determine the level of maternal knowledge about healthy food for preschool children in kindergarten Happy Surabaya. Design used in this study was a descriptive design with a total sampling method, the variable used is a single variable. Population of 41 respondents. Data collected by questionnaires was processed manually, including analyzing the results, giving the code, and enter data into a frequency distribution. The results of this study illustrate all the mothers in kindergarten Happy Surabaya has a good knowledge (92,6%). So the mothers knowledge about healthy food can be inferred either knowledgeable.Keywords: Knowledge, Health Food